Kajian Kandungan Unsur Hara Mikro Pada Lahan Bekas Banjir Lahar Dingin Di Nagari Limo Kaum Kabupaten Tanah Datar - Hidayati, Helsa; Yasin, Syafrimen; Gusnidar, Gusnidar (WBS Laboratory, 2025)
Cold lava floods contain volcano material that is rich in micronutrient which will gradually release through weathering process. The study of micronutrient elements affected by cold lava floods was conducted in Nagari Limo Kaum, Tanah Datar Regency, from October to March 2025. This research was aimed to assess and analyze the content of micronutrients (Fe, Mn, Cu, Zn, Mo and B) in land impacted by cold lava floods in Nagari Limo Kaum, Tanah Datar Regency. The study was carried out using a survey method. Soil samples were collected using purposive sampling from lava deposit (Locations 2, 3, and 4), areas affected by floodwater flow without deposition (Location 5), and unaffected areas (Location 1) as a comparison. Soil samples were collected from 0-20 cm soil depth at each location with 3 replicates. The analyzed parameters included soil pH, cation exchange capacity (CEC), exchangeable aluminum, and micronutrients (Fe, Mn, Cu, Zn, Mo and B). The results showed that increased the micronutrient content and exchangeable aluminium, increased while Zn and B content had low to very high criteria. The chemical properties especially pH and CEC of the soil at L1 and L5, were lower that those at impacted soils.